Haemato-biochemical Profile of Haemoprotozoan Infected Cows, Buffaloes, and Horses - Odedara, Arjun B.; Thakre, Bhupendra J.; Padodara, Ramesh J.; Kalaria, Vinay A.; Singh, Vivek K.; Vasava, Amrita A.; Sharma, Arun K. (Indian Journal of Veterinary Sciences and Biotechnology, 2021)
The present study was conducted to evaluate haematological and biochemical alterations in haemoprotozoan infected animals (n = 60; cows 20, buffaloes 20 and horses 20) compared to healthy ones (n= 20, 20 & 20, respectively) in and around Junagadh region in Gujarat. There was a significant (p<0.01) decrease in Hb, PCV, TEC, MCHC, platelet count, and lymphocyte % with the increase in TLC and neutrophils in all three species of animals affected with haemoprotozoan diseases as compared to healthy counterparts. Similarly, blood glucose, total protein, albumin, and SOD decreased significantly (p<0.01). At the same time, serum AST, BUN, and LPO increased significantly in infected than the healthy cows, buffaloes and horses, except for DLC and ALT in cows and buffaloes, where the values did not differ significantly between healthy and infected groups. The results, in general, revealed that the haemoprotozoan infection in cows, buffaloes, and horses causes anemia, negative energy balance, liver impairment, oxidative stress, and oxidative damage.